E-learning issues and solutions for students with disabilities during COVID-19 pandemic: Al-Zaytoonah University of Jordan case study - Amal Qassed Ahmad; Khalid Mohammad Jaber; Mohammad Abdul Jawad (International Journal of Evaluation and Research in Education (IJERE), 2022)
In this research, approaches to making e-learning accessible to students with impairments were studied based on the authors’ experience at Jordan’s Al-Zaytoonah University. The educational, organizational, and instructional concerns are underlined when analyzing the university’s experience in giving access to online content. Furthermore, these difficulties must be addressed in order to create the necessary organizational change to effectively solve accessibility concerns. This study looked into the e-learning issues that 56 university students with disabilities had reported. Students reported issues with: accessibility to websites and learning course management systems; accessibility to digital audio and video; time management in completing online tasks; trouble handling data during lectures; and a lack of appropriate adaptive strategies in online questionnaires. Students also noted technical issues with using e-learning, instructors’ communication with e-learning, and their treatment of all students equally, overlooking the necessity of considering the needs of students with impairments. In this study, we present the problems raised by students with disabilities and how the e-learning affects students’ outcomes in the e-learning experience. We also make recommendations based on the students’ realistic special-needs experience at Al-Zaytoonah University in Jordan during the COVID-19 pandemic to inspire decision-makers in educational institutions and those interested in this field.